2017
DOI: 10.7150/thno.20654
|View full text |Cite
|
Sign up to set email alerts
|

Glycan and Peptide IgE Epitopes of the TNF-alpha Blockers Infliximab and Adalimumab - Precision Diagnostics by Cross-Reactivity Immune Profiling of Patient Sera

Abstract: Biological drugs like therapeutic antibodies are widely used for the treatment of various diseases like inflammatory disorders and cancer. A drawback of these novel treatments is the substantial proportion of patients experiencing adverse reactions such as loss-of-drug effect or hypersensitivity reactions. These reactions are associated with pre-existing and/or developing anti-drug antibodies. Especially IgE development is a risk factor for life-threatening systemic anaphylaxis.Methods: In order to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Assays of cross-sectional clinical samples can identify patterns associated with disease states, and longitudinal samples from the same subject can illustrate epitope drift during the course of treatment, e.g., immunotherapies following antibody detection. Such array analyses have proven valuable in vaccine studies [118,119] and in profiling of autoimmune disorders, infections and cancer [117], and they may also be applied to characterize ADAs [120]. Some promising recent developments include combination of peptide array data with results of phage display, protein structural information, B-cell epitope prediction algorithms, etc.…”
Section: Identifying and Modifying B-cell Epitopes In Biotherapeuticsmentioning
confidence: 99%
“…Assays of cross-sectional clinical samples can identify patterns associated with disease states, and longitudinal samples from the same subject can illustrate epitope drift during the course of treatment, e.g., immunotherapies following antibody detection. Such array analyses have proven valuable in vaccine studies [118,119] and in profiling of autoimmune disorders, infections and cancer [117], and they may also be applied to characterize ADAs [120]. Some promising recent developments include combination of peptide array data with results of phage display, protein structural information, B-cell epitope prediction algorithms, etc.…”
Section: Identifying and Modifying B-cell Epitopes In Biotherapeuticsmentioning
confidence: 99%
“…We employed serum from peanut-allergic patients which had been shown beforehand to have a high specific IgE reactivity against the major peanut allergen Ara h 2 ( Table 2 ). Applying a microarray-based epitope mapping technique ( 27 , 28 ) we could identify several linear epitopes on Ara h 2 which are recognized by these IgE (data not shown). Based on these mapping experiments, we chose the 8mer R-D-P-Y-S-P-S-P as typical Ara h 2 epitope, which also encompasses two of the three immunodominant Ara h 2 epitopes previously described ( 37 ) and which reacted with all sera used by us (three different peanut-allergic donors, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Total IgE content and specific IgE reactivity against the peanut allergen Ara h 2 were determined by ImmunoCAP assays (ThermoFisher Scientific/Phadia, Freiburg, Germany). Recognition of linear Ara h 2 epitopes by IgE from patient sera was resolved by in-house epitope mapping analysis as described before ( 27 30 ). Use of patient material for this study was approved by the ethics committee of the University of Luebeck (approval number 10-126).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in the case of anti-TNF antibodies, ADA characterization showed that 90% of antiinfliximab antibodies are neutralizing and more than 97% of anti-adalimumab antibodies are also neutralizing (4). Studies exploring peptide sequences targeted by these ADAs identified B-cell epitopes notably on infliximab and adalimumab variable regions, close to the paratope (5,6). ADA development may lead to reduced BP serum concentrations due to the formation of immune complexes and a loss of efficacy (7) or adverse effects such as infusion reactions (8), cytokine release syndrome (9), or hypersensitivity reactions (2,10).…”
Section: Introductionmentioning
confidence: 99%